The Factors on Labor and Delivery Duration Among Births and Hospitalization Records: The Application of Survival Analysis - Astawa, I Gusti Made Yoga; Lukman, Iing; Aryawati, Wayan (Balai Publikasi Indonesia, 2023)
During labor and delivery has a risk of morbidity and mortality to the mother and the fetus. The length of duration process is one of the causes of maternal and fetal morbidity and mortality. Several cases reported of prolonged labor and delivery duration at Mutiara Bunda hospital, Tulang Bawang Lampung had been increasing in the first quarter of 2014 which caused 66.67% neonatal deaths, indicating 29.61% cesarean section and vacuum extraction. The aim of the study was to find out the factors on labor and delivery duration among births and hospitalization records: The application of survival analysis. A quantitative observational analytic study with a design retrospective cohort, using secondary data from births and hospitalization records: The application of survival analysis. The birth recorded from January to December 2013 and the Sample of 205 medical record taken by Circular Systematic Sampling. The research variables were labor and delivery duration, risk status mother's age, parity, Hemoglobin concentration, blood pressure, uterine contractions, and the baby's weight. Data were analyzed using survival analysis by method the cox proportional hazards regression analysis, consisting of univariate, bivariate, and multivariate analysis. Finding of 66.3% women who experienced spontaneous onset of labor with a median duration of labor of 7.50 hours, the fastest delivery time was 1.08 hours from admission to placental delivery spontaneously with or without curing (the longest 22.75 hours); mother's age without risked status category of 81%; parity of 52.7% multiparous, Hemoglobin concentration of 75.1% had an abnormal, blood pressure of 63.9% had a normal, uterine contractions of 52.2% was adequate, infant weight 55.1% ≤ 3000 grams. There was a relationship factors a parity (p = 0.003, HR = 0.595), uterine contractions (p = 0.013, HR = 0.664) and the labor and delivery duration. Parity was the most dominant variable, and following by uterine contractions, related to labor and delivery duration. The Function model hazard maternity consisted of two variables without effect of interaction variables, parity (p = 0.007, HR = 0.617) and uterine contractions (p = 0.025, HR = 0.672). It is recommended, for hospital management to periodic monitoring and evaluation of midwifery services according to Minimum Service Standards and Standard Operating Procedure, continuous identification of progress in labor and the well-being of mother and fetus, feeling safe and comfortable for patients, increasing patient and family knowledge, increasing preventive promotive efforts, increasing capacity and officer abilities.